2006
DOI: 10.1016/j.bbadis.2005.11.009
|View full text |Cite
|
Sign up to set email alerts
|

A yeast-based model of α-synucleinopathy identifies compounds with therapeutic potential

Abstract: We have developed a yeast-based model recapitulating neurotoxicity of alpha-synuclein fibrilization. This model recognized metal ions, known risk factors of alpha-synucleinopathy, as stimulators of alpha-synuclein aggregation and cytotoxicity. Elimination of Yca1 caspase activity augmented both cytotoxicity and inclusion body formation, suggesting the involvement of apoptotic pathway components in toxic alpha-synuclein amyloidogenesis. Deletion of hydrophobic amino acids at positions 66-74 in alpha-synuclein r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 28 publications
2
59
1
Order By: Relevance
“…71 Two studies confirmed that treatment of yeast cells with ferrous ions triggered an increase in oxidative stress concomitant with enhanced inclusion formation and toxicity of a-syn. 38,72 One of these studies also identified the flavonoids quercetin and (À)-epigallocatechin-3-gallate as compounds that efficiently counteract a-syn toxicity in non-treated yeast cells. 72 As both compounds have strong antioxidant properties, this indicates that a-syn expression by itself augments oxidative stress in yeast, similar to what has been reported to occur in neuronal cells.…”
Section: A-syn Toxicity and Vesicular Trafficking In Yeastmentioning
confidence: 99%
“…71 Two studies confirmed that treatment of yeast cells with ferrous ions triggered an increase in oxidative stress concomitant with enhanced inclusion formation and toxicity of a-syn. 38,72 One of these studies also identified the flavonoids quercetin and (À)-epigallocatechin-3-gallate as compounds that efficiently counteract a-syn toxicity in non-treated yeast cells. 72 As both compounds have strong antioxidant properties, this indicates that a-syn expression by itself augments oxidative stress in yeast, similar to what has been reported to occur in neuronal cells.…”
Section: A-syn Toxicity and Vesicular Trafficking In Yeastmentioning
confidence: 99%
“…97 Several potent compounds of different chemical nature have been identified, including natural polyphenol derivatives present in green tea 96 that were identified independently using different in vitro-based approaches. 98 Importantly, these compounds were successfully validated in fly and neuronal culture models, confirming the outstanding potential of the yeast system for initial inexpensive high-throughput screenings.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast models of neurodegenerative diseases have been successfully employed to identify small molecules capable of ameliorating or reversing toxicity in yeast associated with expression of α-synuclein 33,96 and the polyglutamine-expanded fragment of the human Huntingtin protein. 97 Several potent compounds of different chemical nature have been identified, including natural polyphenol derivatives present in green tea 96 that were identified independently using different in vitro-based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of the human a-synuclein in yeast has lead to the identification of a pathway that is potentially responsible for the cellular toxicity in Parkinson's disease. [20][21][22] Studies of the yeast prion Sup35 provided evidence for the first time that the prion form(s) of the protein may play a physiological role in cell function (e.g., adaptation to the changing environment). 23 Subsequently, the prion form of the human PrP protein has been implicated in the normal process of long-term memory formation.…”
Section: Introductionmentioning
confidence: 99%